Organizational and Economic Forms and Effective Methods of State Regulation of Agriculture - Gataullin, Rinat Fazltdinovich; Askarov, Almir Akhtyamovich; Khuzhakhmetova, Gulnara Nurgaleyevna; Yarkov, Nikita Vladimirovich (Economy of Regions, 2015)
The multistructurality and variety of organizational and economic forms of business pattern in agriculture are reasonably related and presented in the form of the individual and private, collective, state, and also mixed business. The individual and private type of small rural business is country farms and those personal farms, which have commodity or partially commodity character. Collective business in agro-industrial sector of the Republic of Bashkortostan is conducted on the basis of collective-share and cooperative property. All republic agricultural organizations belong to cattle breeding, cattle breeding grain, and grain cattle breeding types, at various combinations of other industries, traditional for the republic as additional. The cattle breeding of milk and meat direction is characterized for all zones of the Republic. Different organizational and economic forms of enterprises have various level of efficiency. The existing experience confirms higher efficiency of large-scale enterprises in comparison to small-scale that is determined by the economic law of production concentration (density, scale), that is economy of scale. There are also distinctions in indicators of farm efficiency. The purpose of the work is the proposal development on creation of the effective agriculture support mechanism. In preparing the study, the methods of statistical data analysis, material analysis of reports of some farms for 2006-2013, also their inspections, indicators of budget performance of the Republic, SWOT analysis of the institutional potential assessment of the internal and external factors influencing the agro-industrial complex strategy development are used. Scope of the results: system of state regulation and support of agro-industrial complex taking into account the business patterns existing in agriculture. Conclusions and main results of the analysis: 1. At the present time, various ways in agriculture, at the right choice of specialization are not competitive to each other, therefore, have the equal rights for the state support. 2. The choice of business pattern has to be carried out by each site of agricultural production independently, at own risk. 3. Structurization of functions of various level public authorities and municipal self-government in regulation of agricultural production is required.